Technologie mobilne jako nośnik zmiany – w opinii nauczycieli z czterech krajów europejskich - GALANCIAK, SYLWIA; WEISS, ANNA; JUDGE, MIRIAM (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Sylwia Galanciak, Miriam Judge, Anna Weiss, Technologie mobilne jako nośnik zmiany – w opinii nauczycieli z czterech krajów europejskich [Mobile technologies as a carrier of change – in the opinion of teachers from four European countries]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 23, Poznań 2018. Pp. 203-220. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.12 The article presents partial results of qualitative research conducted among 83 respondents (28 teachers and 55 students) from four European countries, using tablets to work at school. The aim of the research was to recognize the scope of application of mobile technologies by teachers and students and also their opinions on the usefulness of these technologies as a support in the process of education. An image of teachers and students, who realistically assess the advantages and disadvantages of tablets, and who redefine their role in the educational process, emerges from the individual interviews and focus conversations.